2012
DOI: 10.1177/0961203312457718
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of Th17 cells and Th17-related cytokines in the pathogenesis of lupus nephritis

Abstract: T helper type 17 (Th17) cells, a novel distinct subset of Th cell, can secrete interleukin (IL)-17 in humans. Although recent data suggest that Th17 cells and IL-17 play an important role in the pathogenesis of lupus nephritis (LN), the expression of Th17-related cytokines in the kidneys of SLE patients has not been studied in detail. In the present study, we investigated circulating Th17-cell frequencies using flow cytometry and serum Th17-related cytokine levels by enzyme-linked immunosorbent assay (ELISA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
2
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 53 publications
8
103
2
5
Order By: Relevance
“…In this study, we observed increased levels of IL-6 and IL-21 in supernatants of PBMCs from children with LN. This finding is consistent with previous reports from adults with SLE (8,47). Additionally, as recently demonstrated, serum levels of IL-23 are significantly higher in children with active LN than in those with inactive LN or in controls (48).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we observed increased levels of IL-6 and IL-21 in supernatants of PBMCs from children with LN. This finding is consistent with previous reports from adults with SLE (8,47). Additionally, as recently demonstrated, serum levels of IL-23 are significantly higher in children with active LN than in those with inactive LN or in controls (48).…”
Section: Discussionsupporting
confidence: 93%
“…1B). Stat3 is activated by the cytokines IL-6, IL-21, and IL-23 (24)(25)(26), which are highly expressed in patients with SLE (8,27,28). Thus, we measured the levels of IL-6 and IL-21 in supernatants from anti-CD3/CD28-activated PBMCs and found significantly higher concentrations of these cytokines in supernatants from children with LN (mean 6 SD, 22.3 6 9.4 and 26.1 6 11.4 ng/ml, respectively) than in controls (mean 6 SD, 8.6 6 2.7 and 11.3 6 4.7 ng/ml, respectively) (p , 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum soluble receptor of TNFwas elevated in 12 patients with active lupus nephritis compared with inactive SLE and healthy subjects and declined after clinical remission [42]. IL-17 and IL-23 were also elevated in serum and highly expressed in glomerulus of patients with lupus nephritis, suggesting the potential role of IL-23/Th17 axis on SLE with renal involvement [43,44].…”
Section: Chemokines In Glomerular Diseasesmentioning
confidence: 97%
“…Увеличение концентрации ИЛ17 в сыворотках больных СКВ коррелирует с активно-стью и тяжестью иммунопатологического процесса [104][105][106]. Увеличение концентрации ИЛ6, ИЛ17, ИЛ23 в сыворотке крови и уровня циркулирующих Th17-кле-ток при СКВ коррелирует с клинической активностью заболевания и тяжестью поражения почек по данным биопсии [107]. В биоптатах почек у пациентов с волча-ночным нефритом обнаружена инфильтрация Th17-клетками [108,109], а концентрация ИЛ17 в почечной ткани коррелирует с выраженностью микрогематурии, протеинурии, сывороточным уровнем мочевины и кли-нической активностью СКВ [110].…”
Section: болезнь бехчетаunclassified